2021
DOI: 10.1038/s41598-021-83032-3
|View full text |Cite
|
Sign up to set email alerts
|

C-Glucosylation as a tool for the prevention of PAINS-induced membrane dipole potential alterations

Abstract: The concept of Pan-Assay Interference Compounds (PAINS) is regarded as a threat to the recognition of the broad bioactivity of natural products. Based on the established relationship between altered membrane dipole potential and transmembrane protein conformation and function, we investigate here polyphenols' ability to induce changes in cell membrane dipole potential. Ultimately, we are interested in finding a tool to prevent polyphenol PAINS-type behavior and produce compounds less prone to untargeted and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 92 publications
1
15
0
Order By: Relevance
“…The figure shows that the membrane dipole potential exhibited an increasing trend with increasing concentration of cholesterol and exhibited ∼60% increase relative to control POPC membranes (without cholesterol) in the presence of 40 mol % cholesterol . These results are supported by previous observations that suggested cholesterol increases dipole potential in monoolein bilayer and egg PC monolayer and recent observations made with molecular dynamics simulation, , dielectric spectroscopy vibrational spectroscopy, and fluorescence spectrocopy . The ability of cholesterol to increase the dipole potential of membranes could emanate from its unique molecular attributes such as dipole moment perpendicular to the membrane surface or through cholesterol induced changes on membrane organization (e.g., condensation of lipid headgroup area and/or water penetration) .…”
Section: Role Of Cholesterol In Modulating Dipole Potentialsupporting
confidence: 82%
See 1 more Smart Citation
“…The figure shows that the membrane dipole potential exhibited an increasing trend with increasing concentration of cholesterol and exhibited ∼60% increase relative to control POPC membranes (without cholesterol) in the presence of 40 mol % cholesterol . These results are supported by previous observations that suggested cholesterol increases dipole potential in monoolein bilayer and egg PC monolayer and recent observations made with molecular dynamics simulation, , dielectric spectroscopy vibrational spectroscopy, and fluorescence spectrocopy . The ability of cholesterol to increase the dipole potential of membranes could emanate from its unique molecular attributes such as dipole moment perpendicular to the membrane surface or through cholesterol induced changes on membrane organization (e.g., condensation of lipid headgroup area and/or water penetration) .…”
Section: Role Of Cholesterol In Modulating Dipole Potentialsupporting
confidence: 82%
“…44 These results are supported by previous observations that suggested cholesterol increases dipole potential in monoolein bilayer 64 and egg PC monolayer 65 and recent observations made with molecular dynamics simulation, 38,39 dielectric spectroscopy 32 vibrational spectroscopy, 35 and fluorescence spectrocopy. 66 The ability of cholesterol to increase the dipole potential of membranes could emanate from its unique molecular attributes such as dipole moment perpendicular to the membrane surface or through cholesterol induced changes on membrane organization (e.g., condensation of lipid headgroup area and/ or water penetration). 63 In addition, a combination of both these effects could be operative.…”
Section: Potentialmentioning
confidence: 99%
“…The cell-based data of some phytochemicals might be a product of such effects and not caused by specific binding to therapeutic targets. Recent studies have shown that C-glucosylation of polyphenol compounds causes the PAINS effect, while O -glucosylation has no effect on this behavior [ 250 ]. As per previous data [ 250 ], polydatin, an O -glucosylated derivative of resveratrol, is expected to present the same concerns as the aglycone with regards to inducing non-specific reductions in the membrane dipole potential.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that C-glucosylation of polyphenol compounds causes the PAINS effect, while O -glucosylation has no effect on this behavior [ 250 ]. As per previous data [ 250 ], polydatin, an O -glucosylated derivative of resveratrol, is expected to present the same concerns as the aglycone with regards to inducing non-specific reductions in the membrane dipole potential. Therefore, in order to assess if C -glucosylation of resveratrol is able to preserve the promising bioactivities of polydatin described in this review while addressing the mentioned PAINS-related issue, the biological evaluation of this C -glucosyl analog of polydatin is of utmost importance.…”
Section: Discussionmentioning
confidence: 99%
“…PAINS-type behavior causes membrane disruption by decreasing the membrane dipole potential, which affects intracellular signaling pathways. The cell-based data of several natural products are likely to indicate such effects which may not be caused by specific binding to therapeutic targets [ 147 ]. This non-specific/specific targeting of mitochondria by marine compounds should be carefully considered in future studies.…”
Section: Conclusion Challenges and Future Perspectivesmentioning
confidence: 99%